Laju Fotosintesis dan Kandungan Klorofil Kedelai pada Media Tanam Masam dengan Pemberian Garam Aluminium - ELLY PROKLAMASININGSIH; IRFAN DWIDYA PRIJAMBADA; DIAH RACHMAWATI; RETNO PENI SANCAYANINGSIH (Fakultas Pertanian Universitas Udayana, 2012)
The solubility of aluminum (Al) which is high in acid soils is unavoidable. Solutions or strategies thatcan minimize the adverse effect of Al on soybean need to be obtained, by studying the response ofplants to Al. Al intoxication is a limiting factor for plant productivity. The purpose of this research wasto study the effects of salt form of aluminum complexes with organic acids and salts of aluminumcomplexes with inorganic acids on the rate of photosynthesis and chlorophyll content of soybean (Glycinemax) in the acidic growth medium. Research has been carried out experimentally in the greenhouse ofAgriculture Faculty Gadjah Mada University. The design used was Completely randomized design(CRD) with factorial pattern, and two-factors. The first factor was the kind of aluminum salt consistingof three kinds: without Al, Al-nitrate salt and Al-lactate salt. The second factor is the level of mediumacidity (pH) of growth medium with three level of pH value: pH 4, pH 5 and pH 6. Each treatment wasrepeated 3 replications. Variables that were observed included leaf area, the rate of photosynthesis andchlorophyll content. The results showed that the salt form of Al may affect rate of photosynthesis andchlorophyll content. complex Al salt form with organic acids (Al-lactate) can cause photosynthesis ratecompares favorably with the Al-nitrate.